All-polymer photonic sensing platform based on whispering-gallery mode microgoblet lasers. Issue 18 (21st September 2015) - Wienhold, T.; Kraemmer, S.; Wondimu, S. F.; Siegle, T.; Bog, U.; Weinzierl, U.; Schmidt, S.; Becker, H.; Kalt, H.; Mappes, T.; Koeber, S.; Koos, C.
<x xml:space="preserve">Abstract</x> We present an all-polymer photonic sensing platform based on whispering-gallery mode microgoblet lasers integrated into a microfluidic chip.